Teachers’ experiences of delivering youth vaping prevention materials in schools in England and Scotland: A cross-sectional online survey - Ashley Lee; Hannah Walsh; Matilda Nottage; Stephanie Fincham-Campbell; Eve Taylor; Deborah Robson; Mark Conner; Katherine East (PLoS ONE, 2025)
INTENT is an evidence-based smoking prevention programme for secondary school pupils in Great Britain (GB) that was recently expanded to include vaping information. Little research has evaluated GB-specific youth vaping prevention materials. This study assesses teachers’ experiences of delivering INTENT’s vaping prevention materials in England and Scotland. Teachers who delivered INTENT in England/Scotland (N = 45) were surveyed online in 2024, investigating their i) characteristics, ii) experiences of delivering INTENT, iii) perceived impact of INTENT on their pupils, and iv) perceived levels of smoking and vaping in their school. Teachers frequently reported finding pupils possessing/using vapes (51% at least once a week) and perceiving vaping as a problem (96%) in their school, more than cigarettes (4%, 35%, respectively). Teachers had positive or somewhat positive experiences delivering the INTENT vaping prevention materials (96%), perceived that pupils were engaged either ‘a lot’ or ‘somewhat’ (98%), and felt the materials encouraged pupils to make informed choices about vaping (89%). While most teachers reported a change in vaping harm perceptions after INTENT (82%), misperceptions that vaping is equally/more harmful than smoking remained high (65%). A third of teachers did not perceive a change in pupils’ vaping (35.6%) or smoking (26.7%), or did not know (31.1%, 48.9%, respectively). In conclusion, this study found that INTENT shows potential to improve teachers’ knowledge about vaping and smoking and to challenge vaping harm perceptions, and that experiences with delivery and student engagement were positive. Studies evaluating the impact of INTENT and other school-based interventions on school pupils’ vaping and smoking perceptions and behaviours are required.